Development of an Information System for Use by the Micro, Small and Medium Enterprises (MSME) Sector of the Central District of Honduras, 2024. - Cáceres Rodríguez, Berlín Gricel; Flores Huete, Mario Fernando (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To propose and design a market information system for the management of customer databases for the MSME sector of the Central District of Honduras.MATERIAL AND METHOD: It is a research with a mixed approach, descriptive scope, non-experimental design, simple cross-sectional. A questionnaire was applied to 197 companies (15% microenterprises, 57% small enterprises, 29% medium enterprises); the sample selection was through probabilistic-stratified sampling, considering a universe of 13,344 MSMEs in the Central District.RESULTS: The sector faces great challenges, such as: 1) little access to financing (31%), 2) lack of knowledge of digital marketing (27%) 3) low level of use of technology both in its production systems and in the automation of processes (19%) and lack of knowledge in the management of information systems.CONCLUSIONS: A customer information system was designed that implements the billing modules: product management, customer characterization and reports for the development of databases that contribute to increasing the competitiveness and visibility in the short and long term of the sector.
Keywords: Digital marketing; MSME; Social networks; Marketing information system.